Properties of Contextual Memory Formed in the Absence of αCaMKII Autophosphorylation - Irvine, Elaine E (BioMed Central, 2011)
The alpha-isoform of calcium/calmodulin-dependent kinase II (αCaMKII) is a major synaptic kinase that undergoes autophosphorylation after NMDA receptor activation, switching the kinase into a calcium-independent activity state. This αCaMKII autophosphorylation is essential for NMDA receptor-dependent long-term potentiation (LTP), induced by a single tetanus, in hippocampal area CA1 and in neocortex. Furthermore, the αCaMKII autophosphorylation is essential for contextual long-term memory (LTM) formation after a single training trial but not after a massed training session. Here, we show that in the absence of αCaMKII autophosphorylation contextual fear conditioning is hippocampus dependent and that multi-tetanus-dependent late-LTP cannot be induced in hippocampal area CA1. Furthermore, we show that in the absence of αCaMKII autophosphorylation contextual LTM persists for 30 days, the latest time point tested. Additionally, contextual, but not cued, LTM formation in the absence of αCaMKII autophosphorylation appears to be impaired in 18 month-old mice. Taken together, our findings suggest that αCaMKII autophosphorylation-independent plasticity in the hippocampus is sufficient for contextual LTM formation and that αCaMKII autophosphorylation may be important for delaying age-related impairments in hippocampal memory formation. Furthermore, they propose that NMDA receptor-dependent LTP in hippocampal area CA1 is essential for contextual LTM formation after a single trial but not after massed training. Finally, our results challenge the proposal that NMDA receptor-dependent LTP in neocortex is required for remote contextual LTM.